Cryopreservation as a way to improve laboratory germination and germination energy of seeds - Romadanova, N.V.; Arabayeva М.М.; Rymkhanova, N.K.; Baigaraev, D.Sh.; Ramazanov А.К.; Ishmuratova, M.Yu.; Kushnarenko, S.V. (Fundamental and Experimental Biology, 2022)
In all across the world, including Kazakhstan, there is a problem of loss of plant resources biodiversity. Therefore, work is underway to create cryogenic banks, in which long-term storage of plant germplasm is carried out at an ultra-low temperature of –196 °C.For seeds stored in cryogenic banks, it is necessary to study their dormant state and the action of substances that could stimulate their germination. Medicinal plants are important objects for research since the Republic lacks a well-functioning system of industrial cultivation of medicinal plants and the production of pharmaceuticals based on local raw materials. Consequently, scientific information is required on the long-term maintenance of viable seed material and methods of stimulating seed germination. As a result of the experiments, the positive effect of gibberellic acid (GA) and liquid nitrogen (LN) on the increase in the percentage of germination energy (GE) and laboratory germination (LG) of medicinal plants seeds were revealed. On average, after LN exposure to seeds, the percentage of GE increased by 1.4 and LG by 1.5 times. After the exposure to GA, the percentage of GE increased by 1.2 times, and LG by 2.9 times. It was found that, to stimulate GE and LG, it is sufficient to treat seeds with one of the reagents, GA or LN. It was found that the seeds of Silybum marianumlose their germination after storage at a temperature of 1±1 °C for 9 months. The stimulation of GE and LG may require the treatment of freshly harvested seeds with chemical reagents. The effectiveness of the exposure of LN on in vitroseeds GE of Valeriana officinalis and Matricaria chamomilla variety Karagandinskaya by 4.5 and 1.8 times, respectively, was noted. The LG percentage of Valeriana officinalisafter exposure to LN increased by 1.3 times, while the effect of LN on the LG of Matricaria chamomilla variety Karagandinskaya seeds was not observed.